Standard immunosuppressive treatment reduces regulatory B cells in children with autoimmune liver disease - Yuksel, Muhammed; Nazmi, Farinaz; Wardat, Dima; Akgül, Sebahat; Polat, Esra; Akyildiz, Murat; Arikan, Çigdem (Frontiers in Immunology, 2023)
Introduction: Autoimmune hepatitis (AIH) is a chronic liver disease caused by a perturbed immune system. The scarcity of short- and long-term immune monitoring of AIH hampered us to comprehend the interaction between immunosuppressive medication and immune homeostasis. Methods and patients: We recruited children with AIH at the time of diagnosis and at the 1’st, 3’rd, 6’th, 12’th, 18’th, and 24’th month of immunosuppression (IS). We also enrolled children with AIH being on IS for >2 years. Children with drug-induced liver injury (DILI), and those receiving tacrolimus after liver transplantation (LT), were enrolled as disease/IS control subjects. Healthy children (HC) were also recruited. Peripheral blood mononuclear cells (PBMCs) were isolated from all participants. Healthy liver tissue from adult donors and from livers without inflammation were obtained from children with hepatoblastoma. By using flow cytometry, we performed multi-parametric immune profiling of PBMCs and intrahepatic lymphocytes. Additionally, after IS with prednisolone, tacrolimus, rapamycin, or 6-mercaptopurine, we carried out an in vitro cytokine stimulation assay. Finally, Lifecodes SSO typing kit was used to type HLA-DRB1 and Luminex was used to analyze the results. Results: Untreated AIH patients had lower total CD8 T-cell frequencies than HC, but these cells were more naïve. While the percentage of naïve regulatory T cells (Tregs) (CD4+FOXP3lowCD45RA+) and regulatory B cells (Bregs, CD20+CD24+CD38+) was similar, AIH patients had fewer activated Tregs (CD4+FOXP3highCD45RA-) compared to HC. Mucosal-associated-invariant-T-cells (MAIT) were also lower in these patients. Following the initiation of IS, the immune profiles demonstrated fluctuations. Bregs frequency decreased substantially at 1 month and did not recover anymore. Additionally, the frequency of intrahepatic Bregs in treated AIH patients was lower, compared to control livers, DILI, and LT patients. Following in vitro IS drugs incubation, only the frequency of IL-10 producing total B-cells increased with tacrolimus and 6MP. Lastly, 70% of AIH patients possessed HLA-DR11, whereas HLA-DR03/DR07/DR13 was present in only some patients. Conclusion: HLA-DR11 was prominent in our AIH cohort. Activated Tregs and MAIT cell frequencies were lower before IS. Importantly, we discovered a previously unrecognized and long-lasting Bregs scarcity in AIH patients after IS. Tacrolimus and 6MP increased IL-10+ B-cells in vitro.